Gasification of rice hulls and its use as fuel for the gasoline engine - Padullon, David P. (1983)
In this thesis, the investigation of using combustible gas from rice hull as fuel gas engine coupled to an electric generator set is considered. This power system is simple in structure amd easy to operate.
This study also includes the search of a suitable grate for continuous ash removal system since ash accumulation at the fuel bed is high during gasification process. It attempts further to investigate the performance of conventional gas cleaning devices such as the condenser, scrubber and the cyclone dust collector.
The gas producer used in this study was a downdraft, double-fire, suction type gas producer. The method of testing the gas generator was by using the product gas in a 6-cylinder Chevrolet gasoline engine coupled to an alternating current generator with a rated capacity of 10 KW.
For purposes of comparison, the gas engine was operated and tested using producer gas from ipil-ipil wood chips and gasoline fuel. The data obtained from the actual experiments were correlated using Multiple Regression Correlation to construct the graphs and performance curves for evaluation and analysis.
Results show that rice hulls proved to be good biomass fuel for gas generators. However, compared to ipil-ipil, its performance is much lower due to the combustion properties of rice hulls having low carbon content, low density, high ash content, and high gas tar fraction during dry distillation. SO it is considered inferior fuel for gas generation and seldom used. However, there are still many advantages in using rice hulls as fuel.
The problem of high gas tar fraction during dry distillation was solved by the new gas producer design operating on a dual-combustion process, that is, burning the fuel in the primary combustion zone thus producing pyrolysis gas and tar at the secondary combustion zone. Ash accumulation in the fuel bed was solved by providing the reactor with grate mechanisms tested, a collapsible grate with 8 millimeters distance between bars proved to give satisfactory results.
Although results are satisfactory to show producer gas from rice hulls as a possible substitute for gas engine, the ill-effects on the engine have not been found yet. Except during earlier runs when the gas cleaning was so ineffective that tar was sucked with the gas causing the accumulation of tar at the intake ports and clogging-up the intake valves with hardened tar. However, during the later part of the experiments when the new designed gas producer was used together with the use of the train of gas cleaning system, a cleaner producer gas was attained. In spite of this, extension of the study should be undertaken so as to observe the long term effects of running the engine with producer gas.
This study also includes the determination of the proximate analysis and heating value of rice hulls on dry basis. The analysis of the producer gas was not made due to lack of necessary gas analyzer so that gas calorific value was not determined. Instead, estimates for the thermal efficiency of the whole system was deduced to determine the performance when producer gas was used by the engine. Also included in this thesis are computations of the theoretical gas compositions to predict the quality of the producer gas from rice hulls at different values of gasification temperatures.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman
Keywords: Rice hulls gasification; Internal combustion engines, Spark ignition -- Fuel systems